Analyzing the Enablers for Turkish Defence Industry Supply Chains: An Interpretive Structural Modelling Approach - Tırpan, Ozgur (International Journal of Economics and Financial Issues, 2019)
Defense Industry is one of the most important contributors to a country’s power in economic and political domain. In this sector, there is always the need for continuous innovation and modernization parallel to the technological developments. In this context, aim is to improve the supply chain management for Defense Sector with the efforts of providing for it nationally through the life cycle management approach. The purpose of this study is to determine the conceptual enabling factors, the barriers and the targeted dynamics within the supply chain in the context of the Turkish Defense Industry and to create a model that may be useful for it. First, the detailed review of the relevant writings on the concepts affecting the defense industry and supply chain relationship performed. Then, the academic and industrial opinions about the bilateral interaction of these concepts have been obtained and analyzed with the help of Interpretive Structural Modeling (ISM) Method, which chosen as the proper decision making methodology for this work. Thus, a general model for the Turkish Defense Industry Supply Chain is established. In addition, the academic and the industrial views related to these enablers provided to the users separately and comparatively. Keywords: Defense Industry Supply Chain, Defense Industry, Supply Chain Management, Interpretive Structural Modelling, Decision Making JEL Classifications: H56, L10, M10 DOI: https://doi.org/10.32479/ijefi.8085